Hubungan Antara Kemiskinan dan Kejahatan: Analisis Kriminologis dan Implikasinya terhadap Hukum Pidana - Maulana Ruslan, Muhammad Ibnu; Rukman, Auliah Andika; Rahman, Muhammad Ikhwan (RESTORATIVE JOURNAL, 2024)
AbstrackPoverty and crime are interconnected social problems that pose a global challenge, including in Indonesia. Poverty, as a condition of inability to meet basic needs, can be a driving factor for crime. This study aims to analyze the relationship between poverty and crime from a criminological perspective and its implications for criminal law. The research method used is normative juridical with secondary data sources such as legislation, books, scientific journals, and other literature. The results of the study indicate that poverty can influence a person to commit a crime through economic pressure, limited access, an unfavorable environment, and feelings of injustice. The economic theory of crime, social disorganization, and differential association are relevant in explaining this relationship. The implications for criminal law include the need for an evaluation of criminal policies that consider the socio-economic conditions of perpetrators, fair law enforcement, and the effectiveness of criminal sanctions. Rehabilitation, prevention, and restorative justice approaches can be better alternatives than relying solely on repressive law enforcement. This study concludes that understanding the implications of poverty for criminal law is crucial to creating a fairer and more effective justice system.Keywords: Poverty, Crime, Criminology, Criminal Law